Betriebliche Personalpolitik bei heterogenen Arbeitsmärkten - Michael Beckmann; Grit Mühler; Bernd Schauenberg (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
– The objective of this paper is to analyse the flexibility opportunities of firms to respond to increasing labour market requirements and heterogeneity. Thereby, we focus on two groups of workers and two kinds of management events. The two groups of workers are female and older workers, while continuous training and the use of flexible working contracts (i.e. fixed-term employment, temporary agency work) represent our two kinds of management events. On the basis of large individual- and firm-level data sets we find evidence in line with a gender-biased technological and organisational change in favour of female workers and an age-biased technological and organisational change at the expense of older workers. Furthermore, the use of continuous training, fixed-term contracts and temporary agency workers appears to be beneficial for both labour market participants, i.e. firms and workers. Our results enable firms to respond more effectively to labour markets shortages caused by demographic developments or labour supply changes.
Additional information: An Erratum to this article was published on 03 June 2011: https://doi.org/10.1007/s12651-011-0085-3
Keywords: J31; J51; J52; C21; 330; Personalpolitik; Arbeitskräftenachfrage; erwerbstätige Frauen; ältere Arbeitnehmer; betriebliche Weiterbildung; Heterogenität; Arbeitsmarkt; Leiharbeit; befristeter Arbeitsvertrag; Personalanpassung; technischer Wandel; organisatorischer Wandel; Beschäftigungseffekte; Qualifikationsstruktur; atypische Beschäftigung; IAB-Betriebspanel; IAB-Linked-Employer-Employee-Datensatz